Penangkapan ikan oleh nelayan Negeri Sembilan: Satu kajian empirikal - Abdul Talib, Basri; Jaafar, Abdul Hamid; Siwar, Chamhuri (Universiti Utara Malaysia, 2007)
The objective of this research is to identify the important factors in influencing fishing activities in Negeri Sembilan, specifically in the district of Port Dickson. The study analysed the impact of socio-economics and the environment toward the inefficiency level of the fishing activities as well as to give suggestions to improve efficiency. The Stochastic Frontier and technical inefficiency models were developed to analyse all the data. The results from 156 fishermen show that costs of fishing per trip, number of labour, and type of boat are significant toward the total of landings. Moreover, the study found that the mean of technical efficiency of fishing activities is at 76.5%. Overall, it shows that the efficiency level of fishing activities is moderate and its competitiveness should be improved continuously at the same level with development of other economic activities in this area.